# PRINCIPLE OF MATHEMATICAL INDUCTION EXAMPLES

## About "Principle of Mathematical Induction Examples"

Principle of Mathematical Induction Examples

Here we are going to see some mathematical induction problems with solutions.

Define mathematical induction :

Mathematical Induction is a method or technique of proving mathematical results or theorems

The process of induction involves the following steps.

## Principle of Mathematical Induction Examples

Question 1 :

By the principle of mathematical induction, prove that, for n ≥ 1

1.2 + 2.3 + 3.4 + · · · + n.(n + 1) = n(n + 1)(n + 2)/3

Solution :

Let p(n) =  1.2 + 2.3 + 3.4 + · · · + n.(n + 1) = n(n + 1)(n + 2)/3

Step 1 :

put n = 1

p(1)  =  1.2 + 2.3 + 3.4 + · · · + 1.(1 + 1) = 1(1 + 1)(1 + 2)/3

1  =  1

Hence p(1) is true.

Step 2 :

Let us assume that the statement is true for n = k

p(k) = 1.2 + 2.3 + · · · + k.(k + 1) = k(k + 1)(k + 2)/3  ----(1)

We need to show that P(k + 1) is true. Consider,

Step 3 :

Let us assume that the statement is true for n = k + 1

p(k+1)

1.2 + 2.3 + · · · k(k + 1) + (k+1).(k + 2) = (k+1)(k+2)(k+3)/3

By applying (1) in this step, we get

Hence, by the principle of mathematical induction for n ≥ 1

1.2 + 2.3 + 3.4 + · · · + n.(n + 1) = n(n + 1)(n + 2)/3

Question 2 :

Using the Mathematical induction, show that for any natural number n ≥ 2,

(1 − 1/22) (1 − 1/32)(1 − 1/42) ...............(1 − 1/n2) =(n + 1)/2n

Solution :

Let p(n)  =  (1 − 1/22) (1 − 1/32)(1 − 1/42) ...............(1 − 1/n2)

Step 1 :

(1 − 1/22) (1 − 1/32)(1 − 1/42) ...............(1 − 1/n2) =(n + 1)/2n

put n = 2

p(2)  =  (3/4) =  3/4

Hence p(2) is true.

Step 2 :

Let us assume that the statement is true for n = k

(1 − 1/22) (1 − 1/32) ..................(1 − 1/k2) =(k + 1)/2k  --(1)

We need to show that P(k + 1) is true. Consider,

Step 3 :

Let us assume that the statement is true for n = k + 1

p(k+1)

(1 − 1/22) (1 − 1/32) ................(1 − 1/k2) + (1 − 1/(k+1)2)

=  (k + 2)/2(k + 1)

By applying (1) in this step, we get

(k + 2)/2(k + 1)  =  (k + 2)/2(k + 1)

Hence, by the principle of mathematical induction natural number n ≥ 2,

(1 − 1/22) (1 − 1/32)(1 − 1/42) ...............(1 − 1/n2) =(n + 1)/2n

After having gone through the stuff given above, we hope that the students would have understood "Principle of Mathematical Induction Examples"

Apart from the stuff given above, if you want to know more about "Principle of Mathematical Induction Examples". Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

## Recent Articles

1. ### SAT Math Videos

May 22, 24 06:32 AM

SAT Math Videos (Part 1 - No Calculator)

Read More

2. ### Simplifying Algebraic Expressions with Fractional Coefficients

May 17, 24 08:12 AM

Simplifying Algebraic Expressions with Fractional Coefficients

Read More

3. ### The Mean Value Theorem Worksheet

May 14, 24 08:53 AM

The Mean Value Theorem Worksheet

Read More